UNIVERSITY NOTES. (The Accounting Review, 1928)
Abstract The article presents recent developments in departments related to accounting and economics in several universities and colleges across the U.S. In the absence of Dean E. W. Lord and Assistant Dean R. Davis during the second semester of Boston university, Boston, Massachusetts, Professor Atlee L. Percy of the accounting department has been named acting dean of the College of Business Administration. Professor Percy has thus been appointed Chairman of the Educational Committee of the Massachusetts Society of Certified Professional Accountants (CPA). At the University of California, Los Angeles, California, A. Frank Lloyd, a teaching fellow, has joined the staff of Mclaren, Goode and Co., CPA's. Morris H. Harrison, W.D. Moore and Sterling Reece have been appointed teaching fellows to fill vacancies. Professor Gordan A. Watkins has been acting chairman of the Economic Department during the absence of Professor H.S. Noble. H.E. Crawford, assistant in accounting at the University of Illinois, Chicago, Illinois, has been joining the staff of Arthur Anderson and co. at Kansas City, Kansas. Edwin L. Theies has been coming to the department as assistant professor.